Kupres, Bosnien-Herzegowina: Von der Natur- zur Kultur- zur Rituallandschaft - Müller-Scheeßel, Nils (e-Forschungsberichte des DAI, 2023)
In the last years surveys as well as palynological and geophysical prospections were carried out in the high plain of Kupres, Bosnia-Herzegovina. A newly available 14C-date suggests human usage of the plain already during the Eneolithic. During the Bronze Age the plain seems to have taken on a sacred aspect, as grave mounds were built, most of them visible from quite far away. This suggests a significant opening of the landscape, which is confirmed by pollen analysis. Two probably contemporaneous hilltop settlements were placed so that the largest part of the mounds was not visible from there.